Pengenalan Bagaimana Menjaga Diri Bahaya Bullying Dan Game Online Pada Anak Sekolah Dasar - Mohamad Novaldi Napu; Paramita Arsyad; Bayu Dwisetyo; Rivai Mangumpaus; Anjas Umasangadji (Universitas Muhammadiyah Manado, 2024)
The word bullying comes from English, namely from the word bull, which means a bull who likes to butt heads here and there. this term was eventually taken to describe a destructive act. Meanwhile, according to the Big Indonesian Dictionary (KBBI), the term bullying is the equivalent of bullying. Bullying comes from the word rundung which means to disturb, constantly bother, make trouble. Bullying means the process, method, act of bullying which can be interpreted as someone who uses force to hurt or intimidate people who are weaker than the perpetrator of the bullying (Sripurwaningsih, 2017). According to Kim et al (Anhar, 2014) online games are games where people can play at the same time via an online communication network (LAN or internet). Young (Andrew, 2017) stated that online games are games that are played online via the internet.